The Impact of Product Quality and Service Quality on Client Loyalty and its Effect on Purchase Decision - Christian Kuswibowo; Avia Enggar Tyasti (International Journal of Integrative Sciences, 2023)
This study aims to analyze the impact of product quality and service on customer loyalty and purchase terms. Clients of PT Karya Laksana are the subjects of this study. The study was conducted with 150 respondents using quantitative descriptive methods. The sample length uses a purposeful sampling method that pays special attention to finding patterns. The survey method used when collecting data using a questionnaire tool. So-called structural equation modeling (SEM) is used in this study using the smart-PLS analysis tool. This study proves that product quality has a positive and vital impact on customer loyalty, service quality has a positive and critical impact on customer loyalty, customer loyalty has a positive and essential impact on purchase terms, product quality has a positive and critical impact on customer loyalty Loyalty has a positive and significant impact. Product terms and rate have a positive and significant impact on purchase conditions